Telerehabiltation in Italy During the COVID-19 Lockdown: A Feasibility and Acceptability Study - Giada Milani; Giulia Demattè; Matilde Ferioli; Giulia Dallagà; Susanna Lavezzi; Nino Basaglia; Sofia Straudi (International Journal of Telerehabilitation)
This study examined the feasibility and acceptability of a telerehabilitation program during the COVID-19 pandemic in a sample of adult patients with physical disabilities. Of the twenty-three patients enrolled, 11 agreed to participate in a video-based telerehabilitation program. Barriers and facilitators to the adoption of telerehabilitation were identified and clinical, demographic, and psychological variables were analysed as predictors of success. Age, cognitive reserve, and resilience were significant predictors of satisfaction with telerehabilitation (p<0.05). The telerehabilitation program was perceived as feasible and was well accepted by patients, despite some technology challenges. However, patients who took advantage of telerehabilitation perceived differences in the quality of service and preferred traditional in-person treatment to service delivery via telerehabilitation.